Validity and reliability of the Depression Information Needs Scale among the Iranian general population - Jafari, Alireza; Naddafi, Fatemehzahra; Nejatian, Mahbobeh; Charoghchian Khorasani, Elham; Tehrani, Hadi (Frontiers in Psychiatry, 2024)
Introduction The prevalence of depression in the community is high. Therefore, it is necessary to examine the information needs on depression in the community. This cross-sectional study aimed to translate and evaluate the psychometric properties of the Depression Information Needs Scale (DINS) among the general population. Methods The translation and assessment of the validity and reliability of the DINS were conducted from February 2022 to May 2023 in Gonabad, Iran. The inclusion criteria in this study were individuals 18 years or older, those living in Gonabad for 1 year or more, and participants who provided written informed consent. Sample sizes of 546 and 629 were used for the exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), respectively. The reliability of the DINS was examined using three methods: McDonald’s omega coefficient, test–retest reliability, and Cronbach’s alpha coefficient. Results Most participants were women, had a bachelor’s degree, and were married. The values of 0.959 for scale content validity index averaging (S-CVI/Ave) and 0.817 for content validity ratio (CVR) were calculated. In the EFA section, four factors with eigenvalues greater than 1 were extracted and explained 63.861% of the variance. Only two items were not placed in related or acceptable factors and were deleted. Finally, based on the results of the goodness-of-fit indexes (e.g., RMSEA = 0.074, CFI = 0.944, NFI = 0.930, and GFI = 0.911), the scale was approved with 18 items and 4 factors: lived experience (4 items), general (facts about depression) (6 items), research and policies (4 items), and specific treatments (4 items). For all the DINS items, the McDonald’s omega coefficient, Cronbach’s alpha coefficient, and Intraclass Correlation Coefficient (ICC) were 0.953, 0.950, and 0.957, respectively. Conclusion The Persian version of the DINS was validated with 18 items and 4 factors, and this scale can be used to assess depression information needs in the general public and specific groups.